2017
DOI: 10.1542/peds.2016-4266
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Child Lead Poisoning Case Ascertainment in the US, 1999–2010

Abstract: Based on the best available estimates, undertesting of blood lead levels by pediatric care providers appears to be endemic in many states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Safe housing efforts that include the abatement, remediation, and prevention of environmental Pb hazards in older housing may therefore not be reaching young Black children in as equitable of a manner as their peers. Higher rates of substandard housing conditions afforded to Black families has previously been suggested to significantly contribute to early childhood blood Pb disparities [38,74]. Black children are more likely to reside in homes with leaded paint hazards and are exposed to more household Pb dust [67][68][69].…”
Section: Safe Housing and Environmental Justicementioning
confidence: 99%
See 1 more Smart Citation
“…Safe housing efforts that include the abatement, remediation, and prevention of environmental Pb hazards in older housing may therefore not be reaching young Black children in as equitable of a manner as their peers. Higher rates of substandard housing conditions afforded to Black families has previously been suggested to significantly contribute to early childhood blood Pb disparities [38,74]. Black children are more likely to reside in homes with leaded paint hazards and are exposed to more household Pb dust [67][68][69].…”
Section: Safe Housing and Environmental Justicementioning
confidence: 99%
“…Targeted screening of predominantly Black areas at high risk in Chicago, Illinois, during 2001 revealed that nearly two out of three children with an EBLL ≥10 µg/dL were not previously tested and therefore went unidentified until the study had examined them [98]. At the national level, efforts in targeted screening miss one in three children with an EBLL ≥10 µg/dL, while up to two out of three EBLL-positive children in the South are not identified [74]. These conditions disproportionately impact Black children, as they are exposed to greater amounts of environmental Pb and continue to have much higher BLLs than their White or Hispanic peers.…”
Section: Targeted Screening and Public Health Implicationsmentioning
confidence: 99%
“…Local, state, and national childhood blood lead surveillance data are imperfect owing to the reliance on health care providers to identify appropriate children for testing (without sufficient tools to determine a child’s individual risk) and incomplete reporting of test results by clinicians and clinical laboratories to public health departments. 30 …”
mentioning
confidence: 99%
“…28,29 As a result of undertesting of children, it is estimated that the state identifies only 37% of children with BLLs ‡10 mg/dL. 30 There is little evidence that the State's childhood lead database has been used for the planning or evaluation of prevention of lead exposure. Rather, it is narrowly focused on limited investigation of individual cases and addressing sources of exposure only after poisoning has occurred.…”
Section: Childrenmentioning
confidence: 99%